The role of multinational corporations in African dystopias by Lauren Beukes (Moxyland), Paul McAuley (White Devils) and Nick Wood (Water Must Fall). - (:unkn) unknown (My University, 2023)
This article analyzes the role of multinational corporations in the constitution of African dystopias described in Lauren Beukes' Moxyland, Paul McAuley's White Devils and Nick Wood's Water Must Fall. All three works take a critical look at the collusion between multinational corporations and African states. This is a threat to African societies. For these transnational entities, the exploitation or even enslavement of local populations can appear as a necessity or an opportunity to achieve their economic and political objectives. Their possible substitution for the actions or vacancy of African states thus appears in all three works as a key element of an Afro-pessimism that makes the continent the territory of all possibilities, including the apocalypse.
Keywords: African Research